2014
DOI: 10.1371/journal.pone.0092715
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adenosine on Lymphangiogenesis

Abstract: BackgroundThe lymphatic system controls tissue homeostasis by draining protein-rich lymph to the vascular system. Lymphangiogenesis, the formation of lymphatic vessels, is a normal event in childhood but promotes tumor spread and metastasis during adulthood. Blocking lymphangiogenesis may therefore be of therapeutic interest. Production of adenosine is enhanced in the tumor environment and contributes to tumor progression through stimulation of angiogenesis. In this study, we determined whether adenosine affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…In this study, we provide conclusive evidence that signaling through the A2a adenosine receptor promotes lymphangiogenesis in response to inflammation and cancer, thereby favoring tumor cell metastasis to lymph nodes. Our findings support prior work from Lenoir et al, 43 which demonstrated pro-lymphangiogenenic properties of 2-chloro-adenosine in Matrigel plug assays.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we provide conclusive evidence that signaling through the A2a adenosine receptor promotes lymphangiogenesis in response to inflammation and cancer, thereby favoring tumor cell metastasis to lymph nodes. Our findings support prior work from Lenoir et al, 43 which demonstrated pro-lymphangiogenenic properties of 2-chloro-adenosine in Matrigel plug assays.…”
Section: Discussionsupporting
confidence: 92%
“…Sponge assays were performed as previously described (45). In brief, gelfoam sponges (Pfizer, New York, NY, USA) fragments were soaked in conditioned medium.…”
Section: Sponge Assaysmentioning
confidence: 99%
“…ADO is an immunosuppressive metabolite produced at high levels within the TME and contributes, through different mechanisms, to the progression of the tumor itself [ 43 , 44 ]. The effects of a wide range of ADO concentrations (from 10 nM to 100 µM) on U343MG proliferation and viability were evaluated after 24 or 48 h of cell treatment.…”
Section: Resultsmentioning
confidence: 99%